1992
DOI: 10.1177/002199839202600203
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Deformations in C3000/PMR15 Woven Composite

Abstract: An experimental-computational investigation was undertaken to study the behavior of graphite fiber bundles and their influence on each other in C3000/PMR15 woven composite material subjected to compressive loading. Moire interferometry performed on the edge of a [0] 22 laminate showed good correlation of strain distributions with the results obtained from finite element analysis of a ply surrounded with homogeneous material having the smeared properties of the laminate. Furthermore, Moire results clearly revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Although the main compressive failure mechanisms have been identified, failure initiation has not been subject to widespread and detailed study. An exception is the work from Mirzadeh and Reifsnider [9] on the damage initiation and failure in compression of a 8H satin carbon-polyimide material system. Compression tests were stopped before final failure, and the edges of the specimens observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the main compressive failure mechanisms have been identified, failure initiation has not been subject to widespread and detailed study. An exception is the work from Mirzadeh and Reifsnider [9] on the damage initiation and failure in compression of a 8H satin carbon-polyimide material system. Compression tests were stopped before final failure, and the edges of the specimens observed.…”
Section: Introductionmentioning
confidence: 99%
“…The relative positioning of adjacent layers with the same orientation, hereafter referred to as stacking, determines the number of coincident valleys and peaks between adjacent layers and, therefore, affects strongly the degree of nesting. Very few studies have discussed the effect of stacking (and resultant nesting) on the failure of woven composites [9][10][11][12][13]. Breiling and Adams [10], studying the compressive failure of a 5H satin carbon-epoxy, concluded that varying the stacking configuration (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have investigated the effect of stacking (and resultant nesting) on the failure of woven composites (e.g. Refs [39][40][41][42]). Breiling and 7.15 Location of the failure relative to the centre of the crimp region [38].…”
Section: Experimental Observationsmentioning
confidence: 99%